2019
DOI: 10.1016/j.indcrop.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Eschweilenol C in derivative of Terminalia fagifolia Mart. and green synthesis of bioactive and biocompatible silver nanoparticles

Abstract: A green synthetic route was developed to prepare silver nanoparticles (AgNPs) in aqueous solution for biological applications. Eschweilenol C, a compound derivative ellagic acid was identified as the main constituent of the aqueous fraction of the ethanolic extract of Terminalia fagifolia Mart. by NMR analysis. In the green synthesis, the ethanolic extract of T. fagifolia and its aqueous fraction were used to promote silver reduction and nanoparticle stabilization. The synthesized AgNPs presented a spherical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Furthermore, the synthesized AgNPs in presence of T. polium showed an appropriate antibacterial activity comparable to green synthesized AgNPs reported so far 59,60 . Additionally, AgNPs in this study showed a lower minimal inhibitory concentration toward P.aeruginosa compared to S.aureus.…”
Section: Morphology Of Agnps Containing Nanofilmssupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the synthesized AgNPs in presence of T. polium showed an appropriate antibacterial activity comparable to green synthesized AgNPs reported so far 59,60 . Additionally, AgNPs in this study showed a lower minimal inhibitory concentration toward P.aeruginosa compared to S.aureus.…”
Section: Morphology Of Agnps Containing Nanofilmssupporting
confidence: 75%
“…Rodrigues de Araujo et al and Saravanakumar et al also reported a higher antibacterial activity of green synthesized AgNPs against P. aeruginosa compared to S. arouse. The potential reasons for this observation may be attributed to the presence of dense layer of peptidoglycan on the surface of gram-positive bacteria, which undermines the penetration of AgNPs into bacteria and in turn, reduces their antibacterial activates 59,60 .…”
Section: Morphology Of Agnps Containing Nanofilmsmentioning
confidence: 99%
“…There were no correlations between the results obtained, with the values of % inhibition as determined by the ABTS •+ assay being higher (average 78.2 ± 4.1%) compared with that obtained by the DPPH • assay (average 18.4 ± 3.9%). The difference in these values arised from the difference in their principles of actions and the solubilisation of the radicals employed: the DPPH • assay determined the ability of the tested samples that contain phenolic compounds and their derivatives to act as donors of hydrogen to the 2,2-diphenyl-1-picrylhydrazyl free radical, suitable in hydrophobic systems, while in the ABTS •+ assay, an electron-transfer methodthe, the ABTS •+ radical can react with more compounds, both in hydrophilic and hydrophobic systems, and lead to obtaining higher values than those calculated for the DPPH • assay [ 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Filters were tested using previously characterized silver nanoparticles (AgNPs) with ã 140 nm mean size, the approximate size of Sars-CoV-2 (with an average size of 125 nm) [15] and a concentration of 19.10 × 10 9 ± 7.42 × 10 8 particles/mL by nanoparticle tracking analysis (NTA) on Malvern NanoSight NS300 equipment (Malvern Instruments, Malvern, UK), using a 542 nm LASER module and NTA 3.2 software (Malvern Instruments, Malvern, UK) [16]. The test consisted of spraying AgNPs on the filter until saturation.…”
Section: Nanoparticle Filtration Testmentioning
confidence: 99%